Perturbed Angular Correlations - 152Sm and 152Gd - Byrnes, Michael Brian (My University, 1971)
Using the technique of perturbed angular correlations, the rotation of the 4 + 366 keV 152Sm level and the rotation of the 2 + 344 keV 152Gd level was observed. These nuclei were the daughter nuclei of 152Eu, present in the europium - gadolinium and europium - holmium alloys which were commercially obtained (europium concentration was about 1% in both alloys). Anomolously low fields were obtained for 152Gd in gadolinium and in the holmium which raised doubts as to the homogeneity of the alloys.
Samples of the alloys were analysed metallurgically. After chemical treatment and microscopic examination the presence of inclusions was detected. Electron microprobe examinations indicated that the inclusions were europium. The metallurgical analysis confirmed the doubts raised by the nuclear experiments showing that the two methods can be employed complementarily for alloy analysis.
Keywords: perturbed, angular correlations, 152 Sm, alloys, electron, metallurgical